The kindness of strangers : tales of fate and fortune on the road - George, Donald W. (Lonely Planet, 2016)
"A timely collection of 26 inspiring tales, The Kindness of Strangers explores the unexpected human connections that so often transfigure and transform the experience of travel, and celebrates the gift of kindness around the world"--Page 4 of cover.